2006
DOI: 10.1002/ajp.20265
|View full text |Cite
|
Sign up to set email alerts
|

Bed‐building in captive chimpanzees (Pan troglodytes): the importance of early rearing

Abstract: In the wild, great apes sleep in beds they make by successively bending branches into an interwoven platform. These beds are functionally more closely related to human beds than they are to the nests and tree-holes used by other primate species. The idea that bed-building by great apes is learned behavior that is dependent on appropriate early experiences has been proposed but never fully tested. In the present study this hypothesis was indirectly tested in 73 captive adult chimpanzees (Pan troglodytes; 27 wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…Thus, social learning acts to speed up the acquisition of behaviour patterns that are universal in the species concerned and thus probably have an innate component [42][43][44], such as nest building in great apes. It also improves their adult deployment, as shown for nest building in chimpanzees [45,46]. However, social learning also allows acquisition of novel behaviours (innovations) that the animals would not learn at all otherwise.…”
Section: The Cultural Intelligence Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, social learning acts to speed up the acquisition of behaviour patterns that are universal in the species concerned and thus probably have an innate component [42][43][44], such as nest building in great apes. It also improves their adult deployment, as shown for nest building in chimpanzees [45,46]. However, social learning also allows acquisition of novel behaviours (innovations) that the animals would not learn at all otherwise.…”
Section: The Cultural Intelligence Hypothesismentioning
confidence: 99%
“…For physical skills, learned through social information, the effects are stronger. Infant chimpanzees reared without adult role models show much reduced competence in many physical skills, such as nest building [45,46] and tool use [62], or fail to develop them altogether, despite showing otherwise normal behaviour. Thus, primates, especially apes, deprived of adult role models acquire a smaller set of learned skills (see electronic supplementary material for more details).…”
Section: Testing the Developmental Predictionmentioning
confidence: 99%
“…Extensive information can be found about nest construction in great apes (Gorilla: [Dupain et al, 2004;Lukas et al, 2003;Tutin et al, 1995], Pan troglodytes: [Brownlow et al, 2001;Goodall 1962;Stewart et al, 2007;Videan 2006], Pan paniscus: [Fruth, 1995], Pongo pygmaeus: [Ancrenaz et al, 2004;van Noordwijk & van Schaik 2005], but less is known about this behavior in other primates. Usage of nests, however, has been documented in several prosimians over the last decades for example, in Galago senegalensis [Bearder & Doyle, 1974], Daubentonia madagascariensis [Ancrenaz et al, 1994], Mirza coquereli [Sarikaya & Kappeler, 1997], and especially in mouse lemurs (M. ravelobensis [Weidt, 2001], Microcebus murinus [Martin, 1972;Petter et al, 1977;Radespiel et al, 1998Radespiel et al, , 2003] M. rufus: [Martin, 1972;Petter et al, 1977]; Microcebus berthae [Dammhahn & Kappeler, 2005;Kappeler, 1998], but to our knowledge, the actual construction of these nests has only rarely been observed.…”
Section: Introductionmentioning
confidence: 98%
“…Although there is an innate component to nest building in great apes, it is not an entirely instinctive behavior. It has been shown that immature individuals build nests more efficiently and of a higher quality when exposed to nest-building adults (3,4). This indicates a role for learning and innovation in the building of nests (1)(2)(3)(4).…”
mentioning
confidence: 99%